INTERACTIVE TEACHING METHODS IN ENGLISH CLASSES - Turg`unova, Fazilat; Rustamova Shahnoza Abdurahimovna (Журнал иностранных языков и лингвистики, 2023)
The basis of our article The main goal of using interactive methods in distance learning of foreign languages ​​​​is to involve students in the process of active learning and help to develop their knowledge and research skills. Interactive methods are based on an active relationship between teacher and student, with complete mutual understanding. The ultimate goal of introducing interactive methods into the learning process is to organize the interaction of teacher and student in the classroom regardless of the form of teaching.